Soil Infiltration Rate at the Base of Karst Valley in the Gunungsewu Karst, Indonesia - Budiyanto, Eko; Purnomo, Nugroho Hari; Mahardiani, Insan Wastuwidya; Haryono, Eko (Indonesian Journal of Geography, 2025)
The Gunungsewu Karst is a landscape that is highly vulnerable to degradation. Infiltration rate is a critical factor in efforts to protect and conserve karst environments, however, studies focusing specifically on infiltration processes at the valley floor of karst systems, particularly in relation to the morphological characteristics of the Gunungsewu karst, remain limited. This study aims to examine the characteristics of soil infiltration rates at the bottom of the Gunungsewu karst valleys based on their morphological units. Field measurements of infiltration rates were conducted using a double-ring infiltrometer, and infiltration parameters were calculated using the Horton model. Sampling was carried out according to the morphological classification of the Gunungsewu Karst, which includes rounded karst cone units (K1), elongated karst cone units (K2), and trapezoidal karst cone units (K3). Data analysis employed a descriptive approach based on data distribution, visualized using box-and-whisker plots and line graphs.The results indicate distinct differences in infiltration rate characteristics among the morphological units. Infiltration rates across all sites ranged from 0.10 cm min⁻¹ to 0.65 cm min⁻¹. The highest infiltration rates were observed sequentially in the K1, K2, and K3 units. Variations in infiltration rate characteristics within the study area are strongly influenced by morphological features, lithology, vegetation cover, and land use. These findings enhance the understanding of infiltration rate characteristics in karst environments and provide a scientific basis for the development of sustainable strategies for karst environmental protection and conservation.Received: 2025-04-10  Revised: 2025-10-10  Accepted: 2025-12-16 Published: 2025-12-31